Exergy analysis of a four pan jaggery making process - Sanober Khattak; Richard Greenough; Vishal Sardeshpande; Neil Brown (Energy Reports, 2018)
Jaggery is a non-traditional sweetener that is produced from boiling sugarcane juice. Due to the energy intensive nature of the combustion process in jaggery making, previous studies in literature have presented various process and equipment modifications to affect its energy efficiency. This study adds to the understanding of the resource transformations and consumptions in the jaggery process by presenting its exergy analysis. The baseline process was operationally modified for which the exergy efficiency and exergy destruction are calculated. Through the modifications, the exergy efficiency and exergy destruction increased by 11.2% and 0.8% respectively. A significant amount of exergy was wasted as surplus heat in the form of flue gas, which reduced by 11.5% due to process modifications. The results show that while the most evident form of resource waste was due to flue gas released into the environment, the largest form of resource consumption was actually due to exergy destruction arising from irreversibilities in combustion, a result not clearly evident through energy analysis alone. Through modelling process flows in terms of exergy, the analysis presented in this paper increases the visibility of the resource consumptions and losses in the jaggery making process. This study should aid the efforts of researchers and practitioners aiming to reduce resource consumption in the jaggery making process.
Keywords: 330; Energy analysis; Energy reuse; Exergy analysis; Resource consumption; Resource efficiency; Resource efficient manufacturing; Resource flows mapping